A knight of the seven kingdoms [compact disc, unabridged] : being the adventures of Ser Duncan the Tall, and his squire, Egg - Martin, George R. R. (Penguin Random House LLC, 2015)
Taking place nearly a century before the events of A Game of Thrones, this audiobook compiles the first three official prequel novellas to George R. R. Martin's ongoing masterwork, A Song of Ice and Fire. These never-before-collected adventures recount an age when the Targaryen line still holds the Iron Throne, and the memory of the last dragon has not yet passed from living consciousness.